The reader in the book : a study of spaces and traces - Orgel, Stephen (Oxford textual perspectives., 2015)
A study of the archaeology and sociology of the use of margins and other blank spaces. Marginalia constitute a significant dimension of the book's history, and what readers did to books often added to their value. This study deals with books in which the text and marginalia are in intense communication with each other, in which reading constitutes an active and sometimes adversarial engagement with the book. The underlying questions is at what point marginalia, the legible incorporation of the work of reading into the text of the book, became a way of defacing it rather than of increasing its value--why did we want books to lose their history?